Public-Private Partnership as a Model of Financing the Reconstruction of Critical Infrastructure Facilities - A. Artemenko (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article is devoted to the actualization of the development of Public-Private Partnership (PPP) as a key instrument for financing and restoring critical infrastructure facilities in Ukraine under conditions of post-war reconstruction. It is proven that, given the large-scale military destruction and limited budget resources, PPP is an effective mechanism for attracting private capital, optimally allocating risks, and implementing innovative solutions. The aim of the study is the theoretical generalization of existing approaches and the development of a coherent structural model for PPP implementation, intended to combine the economic interests of the state, business, and society for sustainable financing of critical infrastructure. The article analyzes modern scientific approaches to understanding the essence of PPP, which focus on its role in stimulating economic development and increasing the efficiency of infrastructure project development. It is revealed that in practice, the application of PPP often comes down only to financial cooperation, ignoring the significant influence of external political, social, and technological factors. Based on this generalization, key external environmental factors (political-legal, economic, social, and technological) that critically determine the effectiveness of PPP specifically in post-war conditions are systematized. The author proposes a structural model of Public-Private Partnership which includes four interconnected blocks: the analytical-monitoring block (assessment of the external and internal environment), the strategic-planning block (determining the form of PPP, aligning stakeholders' interests), the organizational-implementation block (distribution of resources, functions, and risks), and the control-adaptive block (evaluation of results, performance monitoring, and strategy adjustment). It is proven that the implementation of the model will contribute to increasing transparency, management flexibility, investment efficiency, trust between partners, and the sustainability of post-war recovery processes of critical infrastructure. It is generalized that PPP is a promising mechanism for sustainable financing of critical infrastructure, which ensures a balance between economic expediency and the social significance of projects. The prospects for further research lie in the development of methodological approaches to assessing PPP effectiveness and its integration into national post-war recovery programs.